Mice experimental model of diabetes mellitus type ii based on high fat diet - L. V. Kapilevich; A. N. Zakharova; E. Yu. Dyakova; T. A. Kironenko; K. G. Milovanova; J. G. Kalinnikova; A. V. Chibalin (Бюллетень сибирской медицины)
An experimental model of the obesity and type II diabetes mellitus formation in C57BL/6 mice using a high fat diet was developed and tested. In the study, it was shown that mice feeding high-fat diet had a significant body weight gain during the 3rd week. By the end of the experiment, body weight has more than doubled. In mice that feed chow diet, body weight increased by 50%, by the end of the experiment It was shown that high fat diet also induced glucose tolerance, and the insulin concentration tripled. The data obtained confirm the adequacy of the experimental model of diabetes mellitus type II in mice.